The Origins and Development of the Academic Library Systems Office in Ohio, 1960-1990 - Featherstone, Jan Alyce ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
The purpose of this study is to look at how the academic library systems office (i.e., an entity or group of entities within a library whose purpose is to oversee the hardware and software systems functions within its electronic automated processes and services for the use of the staff and public) in Ohio has evolved to become a library-wide service and to explore the past and present roles and responsibilities of the systems office and its staff in relation to library automation's technological evolution and expansion. The study concentrated on the following three issues: the historical background of the systems office; the professional qualifications of staff; and the job responsibilities of the systems officer and staff. Through an analysis of automation literature and the use of a questionnaire survey, data were obtained and tabulated using the 17 academic libraries involved with OhioLINK as a sample population. The study found that the academic library systems office and staff evolved and expanded simultaneously with library automation technology. The library automation questionnaire is included in the appendix. (Contains 64 references.) (JLB)
ERIC Note: M.L.S. Research Paper, Kent State University.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Libraries; Higher Education; Information Technology; Library Automation; Library Development; Library Networks; Library Personnel; Library Role; Library Services; Library Surveys; Questionnaires; State Surveys; Technological Advancement; Ohio -- OhioLINK; Dissertations/Theses, Masters Theses; Tests/Questionnaires.